2022
DOI: 10.15212/caet/2022/8/1
|View full text |Cite
|
Sign up to set email alerts
|

Artmaking Resilience: Reflections on Art-Based Research of Bereavement and Grief

Abstract: This article presents some of the elements of artmaking as sources of resilience within the process of bereavement and grief. It builds upon findings from an art-based research project conducted during the period of coronavirus disease 2019 pandemic that explored properties of resilience in the face of sickness and death, which suggests three active elements to resilience: the capacity to observe pain, possession of faith, and the support circle. The article ties these findings, with other artistic projects in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Within art-based methodology, artistic expressions serve the researchers and participants for comprehension and assessment (Kossak, 2021;McNiff, 2014). The created artworks represent contents and meanings, emphasizing their significance (Lev, 2021;2022;Duckrow Fonda, 2017). This research echoed other researchers who found the transition between working with clay to the verbal discussions, facilitates expression (Agyei et al, 2021;Govoni et al, 2022) and exposure and transformation of paternal perceptions (Bat-Or, 2010;Bat-Or & Greinmann-Bauch, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within art-based methodology, artistic expressions serve the researchers and participants for comprehension and assessment (Kossak, 2021;McNiff, 2014). The created artworks represent contents and meanings, emphasizing their significance (Lev, 2021;2022;Duckrow Fonda, 2017). This research echoed other researchers who found the transition between working with clay to the verbal discussions, facilitates expression (Agyei et al, 2021;Govoni et al, 2022) and exposure and transformation of paternal perceptions (Bat-Or, 2010;Bat-Or & Greinmann-Bauch, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…They observed and examined the artworks according to the phenomenological-aesthetic approach that traces the nature of the phenomena (Betensky, 1977). They also drew on their observation logs to recall feelings and interpretations stemming from the experiential meeting and the process as a whole (Lev, 2022). Then, they discussed the body of information, distilling the main themes that could answer the research question.…”
Section: Systematic Analysis Of the Research Informationmentioning
confidence: 99%